Crusade: the uses of a word from the Middle Ages to the present - Weber, Benjamin (Crusades - Subsidia, 2024)
"The word 'crusade' covers today a wide variety of meanings in most European languages. The link between these uses and the historical phenomenon labelled as 'crusade', by historians is often very narrow and particularly changing. Understanding the real meaning of the word 'crusade', its connotations and implications, and thus the conscious or unconscious intentions of its uses requires a precise knowledge of the historical evolutions of the word, from its first appearance in the 13th century until nowadays. This book offers the first comprehensive view of the historical construction of the meaning of the word 'crusade' through comparative perspectives from the Middle Ages to the 21st century. Its 11 articles, introduction and conclusion examine different uses of the word, in a single language or within a specific context, and analyze each of them as a different conceptualization of the crusading phenomenon. The book explains the progressive widening of the meaning of the term, from a military expedition to Jerusalem to the most metaphorical uses. It demonstrates the differences between the connotations of the word in various languages and cultures and, thus, the variety of its possible uses. It insists on the reluctance and reticence that 'crusade' has always provoked since the Middle Ages, precisely because the conceptualization it implied was not shared by all. The book will be of interest for crusade scholars and for diachronic linguists, but also for anyone interested in understanding better modern discourses and references to the 'crusade' by politicians, activists, and journalists, through a precise inquiry on the historical developments of the word and the variety of its meanings"--